2016
DOI: 10.4028/www.scientific.net/msf.858.840
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Pit Shape on 4H-SiC MOSFETs Reliability under High Temperature Bias Tests

Abstract: The influence of surface pit shape on 4H-SiC double implanted MOSFETs (DMOSFETs) reliability under a high temperature drain bias test has been investigated. Threading dislocations formed two types of pit shapes (deep pit and shallow pit) on an epitaxial layer surface. The cause of the failure was revealed to be an oxide breakdown above the pit generated at the threading mixed dislocation in both pit shapes. Weibull distributions between two types of pits were different. Although the DMOSFETs on the epitaxial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Figure 4 shows the electric field distributions of C-MOS and the proposed structure in the off state when the V DS is 650 V. According to research [ 23 ], the maximum oxide electric field ( E MOX ) to obtain a lifetime of more than 10 years was estimated to be 2.7 MV·cm −1 in blocking state. Because of the deep P+ shielding layer, both of the structures have a lower electric field than 2.7 MV·cm −1 at the gate oxide.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Figure 4 shows the electric field distributions of C-MOS and the proposed structure in the off state when the V DS is 650 V. According to research [ 23 ], the maximum oxide electric field ( E MOX ) to obtain a lifetime of more than 10 years was estimated to be 2.7 MV·cm −1 in blocking state. Because of the deep P+ shielding layer, both of the structures have a lower electric field than 2.7 MV·cm −1 at the gate oxide.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The influence of surface pit shape on 4H-SiC double implanted metal-oxide-semiconductor field-effect transistor (MOSFETs) reliability under a high temperature drain bias test has been investigated by Uchida. et al [9] in 2015, and the failure was revealed to be an oxide breakdown above the pit generated at the threading mixed dislocation in both pit shapes. Bonyadi.…”
Section: Introductionmentioning
confidence: 93%
“…Too large of a gate oxide field extremely degrades the long-term reliability of the devices. It is found that under a high gate oxide electric field, hot carriers can be trapped in the gate oxide, leading to degraded device characteristics [20], and gate oxide breakdown easily happens with surface pit shape defects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Too high of an electric field in the gate oxide of SiC power devices can reduce the lifetime of the devices. A high electric field in the gate oxide together with SiC surface defects easily lead to the breakdown of the gate oxide [21]. Under too high of a gate oxide electric field, hot carriers are prone to be trapped in the gate oxide, leading to the failure of power devices: for example, the threshold voltage shifting [20].…”
Section: Introductionmentioning
confidence: 99%